Agronegócio e os impactos socioambientais do uso de agrotóxicos na vida de trabalhadores do campo em áreas de produção de milho no município de Carira, SE - Silva, Simone Benedita dos Santos (2015)
The intense use of pesticides in Brazil has caused numerous social, environmental and health impacts, being now a public health problem. Since 2009, our country is the largest consumer of pesticides in the world, staying at the top of the ranking since then. Estimatives show that each Brazilian consumes, in average, 5,2 L of pesticides each year, furthermore, laboratory tests conducted by the Program of Analysis of Pesticide Residues in Food (PARA) reveal high levels of intoxication by this product in basic food provided to society. That way, numerous problems are originated by the use of agricultural pesticides in Brazil, and Sergipe is also harmed by this process. Therefore, the objective of this study was to analyze the social-environmental impacts brought to the life of salaried rural workers and family-based producers in the state of Sergipe, particularly in the city of Carira, caused by the use of pesticides. The city of Carira was chosen because of the fact it is the largest corn producer in the state, hence, a lot of pesticides are used in its tillages. Thus, to understand the socio-environmental impacts originated by the use of pesticides in Sergipe, many interviews were conducted in the city. We interviewed several people directly and indirectly related to the issue of pesticides, such as: family-based producers, rural workers and health, agriculture and environment professionals, besides analysis of legal documents that regulates the use of these products in Brazil and in the state of Sergipe. The qualitative research was of the explanatory type, because it was sought to understand and explain the dynamics of the impacts arising from the use of pesticides in the state. That way, it was found how much the problems originated by the use of pesticides are neglected by the public power in Sergipe, state in which the systematization of the intoxication cases by these products is pratically absent, in other words, we do not have any idea of the real impacts caused by the undiscriminated use of pesticides in Sergipe. Along this research, it was also perceived the strong articulation between Capital, State and Agribusiness in the city of Carira, which is territorialised by the Capital, a fact expressed in the production and enlargement of corn crops, which culminates not only on the strong use of pesticides, but also on genetically modified corn. Thus, numerous difficulties were evidenced along this dissertative research, especially the lack of reliable and official data about the intoxications suffered by family-based producers from Carira by the use of agricultural poison.